2012
DOI: 10.5005/johcd-6-1-28
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Biomarkers: A Periodontal Overview

Abstract: The current clinical diagnostic criterias which were introduced almost half a century ago continue to function as the basis of oral diagnosis in today's clinical practice. Evolvement with time is now brought us to the era of biomarkers. It's a new paradigm for periodontal diagnosis which is of immense benefit in managing periodontitis patients. Biomarkers are tell – tale molecules that can be used to monitor health status, disease onset, treatment response and outcome. These biomarkers can be obtained from blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…The phenotypic markers for junctional and oral sulcular epithelia can be used as indicators of periodontal disease [8]. McLaughlin demonstrated that “the keratin concentration in GCF was significantly higher at sites exhibiting signs of gingivitis and periodontitis compared with healthy sites [81].…”
Section: Proteins Of Periodontiummentioning
confidence: 99%
See 4 more Smart Citations
“…The phenotypic markers for junctional and oral sulcular epithelia can be used as indicators of periodontal disease [8]. McLaughlin demonstrated that “the keratin concentration in GCF was significantly higher at sites exhibiting signs of gingivitis and periodontitis compared with healthy sites [81].…”
Section: Proteins Of Periodontiummentioning
confidence: 99%
“…” Salivary volatiles can be used as possible diagnostic markers in individuals with moderate to severe periodontitis, although no specific association between levels of volatiles and periodontal status has been reported [8]. …”
Section: Proteins Of Periodontiummentioning
confidence: 99%
See 3 more Smart Citations